2015
DOI: 10.1177/1941874415587680
|View full text |Cite
|
Sign up to set email alerts
|

Management of Postthrombolysis Hemorrhagic and Orolingual Angioedema Complications

Abstract: Intravenous recombinant tissue plasminogen activator was first approved for the treatment of acute ischemic stroke in the United States in 1996. Thrombolytic therapy has been proven to be effective in acute ischemic stroke treatment and shown to improve long-term functional outcomes. Its use is associated with an increased risk of symptomatic intracerebral hemorrhage as well as orolingual angioedema. Our goal is to outline the management strategies for these postthrombolysis complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Sources: Foster-Goldman and McCarthy, 158 Gorski and Schmidt, 159 Lewis, 160 Lin et al, 161 Correia et al, 162 O'Carroll and Aguilar, 163 Myslimi et al, 164 and Pahs et al Cryoprecipitate (includes factor VIII): 10 U infused over 10-30 min (onset in 1 h, peaks in 12 h); administer additional dose for fibrinogen level of <200 mg/dL Tranexamic acid 1000 mg IV infused over 10 min OR ε-aminocaproic acid 4-5 g over 1 h, followed by 1 g IV until bleeding is controlled (peak onset in 3 h) Hematology and neurosurgery consultations Supportive therapy, including BP management, ICP, CPP, MAP, temperature, and glucose control AIS indicates acute ischemic stroke; aPTT, activated partial thromboplastin time; BP, blood pressure; CBC, complete blood count; CPP, cerebral perfusion pressure; CT, computed tomography; ICP, intracranial pressure; INR, international normalized ratio; IV, intravenous; LOE, Level of Evidence; MAP, mean arterial pressure; and PT, prothrombin time.…”
Section: † (Class Iia; Loe B-nr)mentioning
confidence: 99%
“…Sources: Foster-Goldman and McCarthy, 158 Gorski and Schmidt, 159 Lewis, 160 Lin et al, 161 Correia et al, 162 O'Carroll and Aguilar, 163 Myslimi et al, 164 and Pahs et al Cryoprecipitate (includes factor VIII): 10 U infused over 10-30 min (onset in 1 h, peaks in 12 h); administer additional dose for fibrinogen level of <200 mg/dL Tranexamic acid 1000 mg IV infused over 10 min OR ε-aminocaproic acid 4-5 g over 1 h, followed by 1 g IV until bleeding is controlled (peak onset in 3 h) Hematology and neurosurgery consultations Supportive therapy, including BP management, ICP, CPP, MAP, temperature, and glucose control AIS indicates acute ischemic stroke; aPTT, activated partial thromboplastin time; BP, blood pressure; CBC, complete blood count; CPP, cerebral perfusion pressure; CT, computed tomography; ICP, intracranial pressure; INR, international normalized ratio; IV, intravenous; LOE, Level of Evidence; MAP, mean arterial pressure; and PT, prothrombin time.…”
Section: † (Class Iia; Loe B-nr)mentioning
confidence: 99%
“…In 2012, the stroke academic industry roundtable suggested beneficial assessment of (1) neuroprotective agents, (2) IV-tPA, and (3) emerging treatments to decrease reperfusion damage. [12345678910111213141516171819202122232425262728293031] Henninger and Fisher reported that <10% of all patients with AIS receive intravenous thrombolysis and it has been expected that only around 7%–15% of AIS patients are qualified for acute endovascular intervention. [29]…”
Section: Discussionmentioning
confidence: 99%
“…Although publication in 2012 stated that IV-rtPA given within 6 h of stroke onset, another publication in 2013 recommended valuable early administration within 0–3 h, destructive later prescription of 3–4.5 h, and again beneficial of administration of 4.5–6 h.[131415] Recent approaches mentioned that IV-rtPA therapy could be administered to cautiously nominated patients who can be treated within 4.5 h of AIS onset. Related to the populations that neurologic signs are revealed on awakening (wake-up stroke), they usually are not given IV-rtPA because of the doubt about the time of stroke onset.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous rtPA was first approved for pharmacotherapy management of AIS in the United States in 1996. Thrombolytic therapy has been established to be effective in acute is-chemic stroke treatment and shown to improve long-term functional outcomes (3). Published literature suggested significant change in large vessel occlusive stroke via extensive use of thrombolysis followed by endovascular clot abolition pharmacotherapy.…”
Section: Contextmentioning
confidence: 99%
“…Table 1 shows the pharmacotherapy properties of tPA. Feared complications include symptomatic intracerebral hemorrhage and orolingual angioedema (3). Hemorrhagic complications such as subarachnoid hemorrhage have been reported (4)(5)(6)(7)(8)(9).…”
Section: Contextmentioning
confidence: 99%